Heat transport and adsorption mechanism of linear alkane liquids on solid surfaces - Rama, Ranjini Devi (2025)
The interaction between solid surfaces and liquid hydrocarbons known as solid-liquid (S-L)interfaces plays a crucial role in various engineering applications that determine the behaviour of liquid orientations which are referred to as adsorption mechanisms. Such interaction is commonly paired with heat transfer at S-L interfaces which are referred to as thermal transport mechanisms. These two important characters are the main contributors to the performances of the S-L interfaces system. The problem arises from the limited understanding of how liquid hydrocarbons behave on solid surfaces during operational conditions, which directly affects their adsorption mechanisms and subsequently their heat transport mechanisms efficiency. Existing studies have primarily focused on experimental methods that do not adequately capture the molecular orientations near the solid surfaces. To address this gap, this study employs nonequilibrium molecular dynamics (NEMD)simulations to analyse the adsorption mechanisms of linear liquid alkane of butane (C4H10) and pentane (C5H12) as they interact with crystal planes of Face-centered cubic (FCC) lattice of (100), (110) and (111). The methodology involves simulating the model that consists of three layers of solid - liquid – solid, with a temperature difference applied across the system to evaluate the heat flux across the systems. To address the adsorption mechanisms the structural properties namely density distributions, orientation order parameter and radius of gyration are evaluated. On the other hand the thermal transport is evaluated based on the temperature distributions and the generated heat flux as the temperature difference is applied across the systems. Molecular dynamics simulations were used to investigate how FCC crystal orientations affect the thermal and adsorption behaviour of C₄H₁₀ and C₅H₁₂ at solid– liquid interfaces. The (111) surface exhibited the highest first adsorption peak at 966.94 kg/m³ for C₅H₁₂, followed by (100) (801.79 kg/m³) and (110) (784.76 kg/m³), corresponding to the number of atoms per layer (224, 200, and 192, respectively). The thermal conductivity for C5H12 is 6.62 × 106 for (100), 6.07 × 106 for (110) and 6.51 × 106 for (111). For C4H10 the thermal conductivity is 5.92 × 106 for (100), 6.08 × 106 for (110) and 5.69 × 106 for (111). In conclusion, C5H10 has a larger adsorption mechanism and higher thermal conductivity as compared to C4H10. The findings contribute to a deeper understanding of interfacial thermal resistance and lay the groundwork for future research aimed at optimising heat transfer in engineering applications involving liquid hydrocarbons.